Solving problems with NMR spectroscopy - Rahman, Atta-ur-, 1942-; Choudhary, Muhammad Iqbal; Wahab, Atia-tul. (United Kingdom : San Diego, CA : Elsevier Academic Press, 2016)
Solving Problems with NMR Spectroscopy, Second Edition, is a fully updated and revised version of the best-selling book. This new edition still clearly presents the basic principles and applications of NMR spectroscopy with only as much math as is necessary. It shows how to solve chemical structures with NMR by giving many new, clear examples for readers to understand and try, with new solutions provided in the text. It also explains new developments and concepts in NMR spectroscopy, including sensitivity problems (hardware and software solutions) and an extension of the multidimensional coverage to 3D NMR. The book also includes a series of applications showing how NMR is used in real life to solve advanced problems beyond simple small-molecule chemical analysis. This new text enables organic chemistry students to choose the most appropriate NMR techniques to solve specific structures. The problems provided by the authors help readers understand the discussion more clearly and the solution and interpretation of spectra help readers become proficient in the application of important, modern 1D, 2D, and 3D NMR techniques to structural studies.
The basics of modern NMR spectroscopy -- Creatin NMR Signals -- Sensitivity Enhancement -- Spin-echo and polarization transfer -- The Second Dimension -- Nuclear Overhauser Effect -- Important 2D NMR experiments -- Playing with Dimensions in NMR Spectroscopy -- Some Key Developments in NMR Spectroscopy -- Logical approach for solving structural problems.
Includes bibliographical references and index.
Keywords: Nuclear magnetic resonance spectroscopy; Nuclear magnetic resonance spectroscopy